2017
DOI: 10.1016/j.ijheh.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

In utero and childhood DDT, DDE, PBDE and PCBs exposure and sex hormones in adolescent boys: The CHAMACOS study

Abstract: Dichlorodiphenyltrichloroethane (DDT), polybrominated diphenyl ether (PBDE) flame retardants, and polychlorinated biphenyls (PCBs) are believed to be endocrine-disrupting chemicals (EDCs) in humans and animals. The purpose of this study is to examine the relationship of in utero and childhood exposure to these purported EDCs and reproductive hormones in adolescent boys who participated in CHAMACOS, an ongoing birth cohort in California’s Salinas Valley. We measured o,p′- and p,p′-DDT, p,p′- DDE, PBDEs and PCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 50 publications
2
34
1
2
Order By: Relevance
“…However, we recently reported that prenatal concentrations of BDE-100 and BDE-153 were positively associated with hormone levels, including testosterone, luteinizing hormone, and follicle stimulating hormone, in 12 year-old boys in the CHAMACOS cohort (Eskenazi et al, 2016), which is consistent with our finding of earlier puberty in boys.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we recently reported that prenatal concentrations of BDE-100 and BDE-153 were positively associated with hormone levels, including testosterone, luteinizing hormone, and follicle stimulating hormone, in 12 year-old boys in the CHAMACOS cohort (Eskenazi et al, 2016), which is consistent with our finding of earlier puberty in boys.…”
Section: Discussionsupporting
confidence: 92%
“…In human studies, prenatal PBDE exposure has been associated with reduced fertility (Harley et al 2010) altered thyroid hormone and sex hormone levels (Chevrier et al 2011; Chevrier 2008; Eskenazi et al 2016; Herbstman et al 2008; Lin et al 2011; Stapleton et al 2011), lower infant birth weight (Harley et al 2011) and impaired childhood neurodevelopment and behavior (Chevrier et al 2013; Eskenazi et al 2013; Herbstman et al 2010; Sagiv et al 2015) but only two studies have examined timing of puberty. Among 271 adolescent girls participating in the National Health and Examination Survey (NHANES), higher serum PBDE concentrations between ages 12 and 19 years was associated with early menarche (<12 years of age) (Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, endocrine disrupting chemicals (EDC), including some phthalates, have been linked to puberty onset [57][58][59] and prenatal EDC exposure has been associated with changes in hormone levels in boys from the CHAMACOS cohort. 60 We found that maternal blood concentrations of brominated diphenyl ether (BDE)-100 and −153 during pregnancy were associated with an increase of the leutenizing hormone levels, and BDE-153 was associated with an increase in testosterone in 12-year-old CHAMACOS boys; while dichlorodiphenyltrichloroethane (DDT), after accounting for Tanner stage, was associated with decreases in the hormone levels. In animal studies, high levels of phthalates have been associated with decreased production of both estrogen and testosterone.…”
Section: Discussionmentioning
confidence: 95%
“…In a study performed in California, USA, higher maternal pregnancy serum PCB levels were found to be associated with higher FSH levels in 12-year-old boys, whereas no associations were found with testosterone or estradiol. 95 In another study performed in the USA, including 10-to 15-year-old children from North Carolina, no significant associations were found between prenatal PCB exposure and stage of pubertal development, as assessed through annual mail questionnaires. 91 In a Taiwanese cohort, the pubertal development of children born to mothers with signs and symptoms of 'Yucheng' oil disease or a history of consumption of the contaminated oil, was compared with the pubertal development of unexposed controls.…”
Section: Effects Of Prenatal Exposure To (Oh-) Pcbs On Pubertal Develmentioning
confidence: 92%